Konsep Dasar Kepemimpinan dalam Perspektif Islam di Era Modern - Kartika, Ika; Aji Budi Santosa; Mahfud Baihaki; Hidin Muhidin; Rima Widia; Fatimah Dzakiroh (Jurnal Dirosah Islamiyah, 2024)
A leader is someone who bears significant responsibilities in an organization or community life. To be a leader, one must possess moral elevation in their way of living, serving as an example for their followers. In Islam, believers are advised to become leaders in accordance with the principles outlined in the teachings of the Islamic faith, leading towards Islamic Leadership (Kepemimpinan Islami). Islamic leadership represents a balance between leadership in the worldly and hereafter context, where the responsibilities of leadership extend not only to the members but also in the sight of Allah SWT.Allah has sent a Messenger, Prophet Muhammad SAW, as an exemplary model for the Islamic community to follow in practicing Islamic Leadership. Islamic leadership prioritizes the values prescribed by Islam, and all actions are undertaken with the hope of attaining Allah's approval. Islamic leadership goes beyond some of the goals pursued in conventional organizational leadership, emphasizing support for the reinforcement of Islamic principles within the organization.Islamic leadership endorses both absolute and authoritative leadership, possessing unique characteristics that differentiate it from conventional leadership. Leaders in Islamic leadership are not merely authoritative figures but also serve as servants for the welfare of the community and the organization they lead.In conclusion, Islamic Leadership is a concept that harmonizes Islamic values with leadership responsibilities. In this context, a leader is expected not only to perform their duties effectively within the organizational sphere but also to uphold moral and spiritual responsibilities in the presence of Allah SWT. Therefore, this article encourages a deeper understanding and application of Islamic Leadership principles to shape organizations that are both integral and morally upright.